RECONFIGURING TRADITION(S) IN EUROPE: An Introduction to the Special Issue. Issue 1 (3rd August 2020) - Isnart, Cyril; Testa, Alessandro
Abstract : "Tradition" has been a key concept and object of European ethnology from the foundation of the discipline all the way to intangible cultural heritage policies today. A focus has been given to the cultural and social circulations and permutations affecting traditional facts and has shown the plasticity of "traditions" to (ever-)changing social conditions. Understood as "uses of the past", these mainly political and sociological understandings of what "tradition" means today need to be complemented with a view on the emotional aspects of this peculiarly human way of imagining and experiencing the world. This text introduces three notions which highlight the experiential dimension of tradition: re-enchantment, ritualization, and heritage-making. We hope to forge new paths towards the exploration of all things "traditional" and their cultural dynamics.